Dampak Industrialisasi Terhadap Pendidikan, Ekonomi, dan Keagamaan Di Desa Banjaran Sumber Jaya Majalengka - Omah Rohmah (IAI Bunga Bangsa Cirebon, 2020)
Industrialization in Indonesia has decreased since the economic crisis in 1998, it's just that this decline does not mean that Indonesia does not have the capital to invest in domestic industries, but rather attacks domestically produced goods. From the above statement and added to our observations conducted in Banjaran Village, then we made a research entitled